Diari e memorie degli emigranti italiani arruolati nella Legione straniera francese (Altre Modernità, 2009)
Since the Seventies, Italian and international historiographies on Italian foreign migration have recourse to the subjective sources as letters, interviews, memoirs, diaries, literature and songs. The present writing relates to the memoirs of the Italian migrants who served in the French Foreign Legion during the XX century. In fact, the enrolment in the Legion was the last device to avoid repatriation in front of the most difficult conditions faced by migrants. The first candidates for the Legion among Italians migrants were, during the Thirties, the ";fuorusciti";, the voluntaries of the international brigades defeated at the war of Spain and especially the Italians menaced of repatriation because of unemployment. Many of them volunteered to obtain naturalization and free access in the French labour market. During the Second World War Italian prisoners of war in French ands enlisted in the Legion to escape the terrible conditions of the camps. Just after the end of the war political and common criminals volunteered, but the most part of the Italians engaged were the clandestine migrants to France who accepted to serve in the Legion to avoid prison and repatriation. Their destiny was to fight in the bloody war of Indochina and in the war of Algeria. Here I present seven memoirs of Italians migrants survived to their service in the Legion, fours of them served between the Thirties and the Second World War and three participated in the wars of Indochina and Algeria.